2022
DOI: 10.1021/acsomega.2c00763
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Precipitation of Lanthanide Oxalates

Abstract: Oxalic acid is an important separation agent in the technology of lanthanides, actinides, and transition metals. Thanks to the low solubility of the oxalate salts, the metal ions can be easily precipitated into crystalline material, which is a convenient precursor for oxide preparation. However, it is difficult to obtain oxalate monocrystals due to the fast precipitation. We have developed a synthetic route for homogeneous precipitation of oxalates based on the thermal decomposition of oxamic acid. This work p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
2
2
0
1
Order By: Relevance
“…A small shift in the v CO band to a higher wavenumber is observed with increased doping concentration. This is in line with previously published results that showed smaller dopants lead to a shift in the spectrum to higher wavenumbers [18,19]. Additionally, a peak around 980 cm −1 is observed for all doped samples, which is not observed in the individual oxalates.…”
Section: Metal Oxalate Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…A small shift in the v CO band to a higher wavenumber is observed with increased doping concentration. This is in line with previously published results that showed smaller dopants lead to a shift in the spectrum to higher wavenumbers [18,19]. Additionally, a peak around 980 cm −1 is observed for all doped samples, which is not observed in the individual oxalates.…”
Section: Metal Oxalate Characterizationsupporting
confidence: 93%
“…As seen, the a and c lattice parameters shrink while b and β stay relatively constant, and a reduction in volume is observed. This is consistent with previous work on lanthanide oxalates that showed a decrease in the a and c parameters with an increase in atomic number through gadolinium for the lanthanides and only a slight change in b and β [18]. The low doping concentrations used here prevent a noticeable trend from being observed for the b and β parameters.…”
Section: Metal Oxalate Characterizationsupporting
confidence: 92%
“…Hal ini karena asam oksalat secara umum memiliki afinitas yang sangat baik dengan LTJ pada umumnya [11]. Oksalat merupakan precursor yang harganya murah tetapi berkualitas tinggi untuk bahan-bahan dengan sifat menarik, seperti bahan bakar nuklir, kerangka logam-organik, oksigen konduktor, atau magnet molecular [12].…”
Section: Asam Oksalat (H2c2o4)unclassified
“…After dissolving the nitrates in water, they were added to a mixture of dissolved oxalic acid in water to precipitate oxalates. The five elements selected (Ce, Pr, Nd, Sm, and Gd) belong to the lanthanide group and all oxalates form in the same structure as decahydrates with space group P2 1 /c [34,35]. Alemayehu et al recently showed that a cerium-gadolinium oxalate could be formed to produce a single phase, homogeneous oxalate [36].…”
Section: Fluoritesmentioning
confidence: 99%